Are independent directors' political connections valuable?: Findings based on a natural experiment in China. Issue 2 (2nd January 2020) - Chen, Yanyu; Zheng, Wenzhe; Huang, Yimiao
Abstract : Purpose: The purpose of this paper is to use difference-in-difference method (DID) to study the influences of independent directors' political connection on firm value. Design/methodology/approach: File No. 18 by the Organization Department of the Communist Party of China Central Committee requires that the leading cadres in party and government offices are not allowed to act as independent directors; this restriction applies to retired officials as well. As a result, many listed companies lose the political connections of officers as independent directors. This paper takes it as an exogenous shock to evaluate the influence of the political connection of independent directors on firm value, effectively alleviating the endogeneity problem existing in previous studies. Findings: The research finds the following: under the policy of compelled resignation, the loss of political connection of independent directors has a prominent negative impact on firm value; and compared to state-owned enterprises, the firm value of private enterprises receives a greater negative impact. However, the political advantage of state-owned enterprises is not obviously influenced. In the regions with worse external market environments, due to a greater reliance on resources brought about by political connection, the policy has a much greater influence on their listed companies. Research limitations/implications: The study faces several limitations, each of which represents a potential research direction. First, our analysis is based on the policy effects on the firm's current Tobin's Q and finds a negative effect of losing political connections. However, the long-term effects are still unclear, as some studies find a negative effect of political connections. Second, the paper focuses on one channel in which political connections may affect firm value. Other channels, such as subsidies and loans from state-owned banks, which need more granular data, should be explored in the future. Practical implications: The use of DID model can better objectively evaluate the implementation effects of ban policies and alleviate endogenous problems, which is also enlightening for further perfection of the system of independent directors in the A-share market. Social implications: It enriches existing researches of the value of independent directors from the perspective of political connection, which is conducive to understanding the influence and channel on the firm value after the loss of political connection and the value of independent directors in the corporate governance in a more comprehensive and accurate manner. Originality/value: This paper extends the relevant research on the value of the political connection of independent directors from the perspective of political connection and enlightens the evaluation of the effect of ban policies.